Second language Reading and Grammar: A Glimpse At Instructional Ideas - Harison Mohd Sidek (Universiti Sains Islam Malaysia, 2022)
﻿This book is divided into two parts; Part I and Part 11. Two instructional approaches are introduced in this book; a text-based discussion approach in Part I and the P-A-C-E grammar teaching approach in Part II. In the first part of the book, the text-based discussion is discussed. This approach is the approach used for reading comprehension in the first language (LI) reading comprehension classrooms as well as in Language Art classrooms. The theoretical underpinning of the approach is described. The description of the instructional design and classroom procedure are presented by taking into account the possible adaptation for second language (L2) classrooms instructional implementation.